Polimorfismos do receptor Mu Opióide (OPRM1) em pacientes com autoagressividade e transtorno do desenvolvimento intelectual - Humberto Ferreira Ianni (2013)
The self-injurious behavior is a frequent and severe clinical manifestation present in a variety of psychiatric disorders. Its prevalence is highly variable, especially due to conceptual and methodological issues. It has been suggested an association between the activity of the opioid system and self-injurious behavior, addictions and social withdrawal. The opioid action can stimulate self-injurious behavior through pleasure reward and pain threshold increase, triggered by the release of endorphins in the brain when performing the acts. There is very little in the literature about an association between genetic polymorphisms of receptors, opioid activity and behavior in patients with intellectual disability. Objectives: This study aims at evaluating the existence of polymorphisms rs1799971 and rs2075572 of the OPRM1 gene in patients with self-injurious behavior and intellectual developmental disorder. Specific objectives were to evaluate the prevalence of self-injurious behavior in patients of specialized institutions; to assess the utility of FAST in detecting the prevalence, frequency and severity of disruptive behaviors, as well as to indicate the most prevalent reinforcement associated with the acts and to analyze the association of genetic polymorphisms with self-injury behavior. Methods: We evaluated subjects with self-injurious behavior in attendance at Censa (Centro Nossa Senhora DAssumpção) in Betim, Fundação Dom Bosco (Units Madre Gertrudes and Floresta), Instituto Pestalozzi, Escola Estadual Dona Argentina, Centro de Saúde Tupi (PBH) and patients from the Ambulatório de Transtornos do Espectro Autista do Serviço de Psiquiatria do Hospital das Clínicas da UFMG. The ABC-C was used to screen for self-injurious behavior; for inclusion in the study, the IBR-MOAS, GSIBS and FAST were used. For genetic analysis, peripheral venous blood samples of patients who met the criteria were collected. Results: Almost a quarter (24.28%) of patients in specialized institutions showed self-injurious behaviors. The FAST showed that the self-injurious behavior occurred in over 80% of cases. The automatic reinforcement of sensory stimulation was the most cited (81,35% of cases). The two investigated polymorphisms were found in the study population. Among patients who had higher frequency of the behavior specified in the item 18 (moderate self-injury) of the IBR-MOAS we observed a higher frequency of genotype C / C (p=0.038). There was also a tendency for genotype C / C to have a higher frequency of the behavior specified in the item 20 (extreme self-injury) (p=0.091). Conclusions: Self-injurious behavior is highly prevalent in institutions specialized in the treatment of patients with intellectual developmental disorder. FAST proved to be useful in assessing the self-injurious behavior and to point the most prevalent reinforcement associated with this act. Among patients with intellectual developmental disorder, the genetic polymorphisms rs1799971 and rs2075572 were found, and those with genotype C/C showed greater association with behavior of the item 18 of the IBR-MOAS, which refers to "hits the head, slams his fist into objects, throws himself into the floor or into objects (hurts, but without serious injury). "